Potensi Pengobatan Tradisional Beluntas (Pluchea Indica L.) Dalam Menurunkan Kadar Trigliserida Dan Glukosa - Aqil, Abiyyu Aditya; Salsabila, Tasya; Lira, Sabilla Nanda; Gibran, Ananda Khalif Pramudya; Giyandari, Senia Angi (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2023)
ABSTRACT Introduction: Indonesia boasts a rich biodiversity and a wealth of medicinal plants, including around 300 species used in traditional medicine. One such popular plant in traditional medicine is beluntas (Pluchea indica L.), known for its various benefits, such as appetite stimulation and its ability to lower blood glucose levels, thanks to compounds like alkaloids and flavonoids. Diabetes mellitus is a serious issue in Indonesia, with a continually rising prevalence, including complications like elevated blood triglyceride levels. Therefore, research on the potential of traditional treatment using beluntas to reduce triglyceride and glucose levels is highly relevant and important. Methods: This research employed a narrative review method. All the literature sources utilized were derived from national and international research articles accessed through search engines such as Google Scholar, PubMed, and Science Direct, as well as the NCBI database. The selected literature primarily comprised journals discussing the biological activities and therapeutic potential of Pluchea indica L., commonly known as beluntas. Furthermore, a descriptive analysis was employed for this study. Result: In vivo testing of the ethanol extract of Beluntas leaves (Pluchea indical L.) was proven to reduce triglyceride and glucose levels. Conclusion: The traditional plant beluntas (Pluchea indica L.) has the potential to reduce triglyceride levels and glucose levels.